6-3(3x-2)=15

Simple and best practice solution for 6-3(3x-2)=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-3(3x-2)=15 equation:


Simplifying
6 + -3(3x + -2) = 15

Reorder the terms:
6 + -3(-2 + 3x) = 15
6 + (-2 * -3 + 3x * -3) = 15
6 + (6 + -9x) = 15

Combine like terms: 6 + 6 = 12
12 + -9x = 15

Solving
12 + -9x = 15

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -9x = 15 + -12

Combine like terms: 12 + -12 = 0
0 + -9x = 15 + -12
-9x = 15 + -12

Combine like terms: 15 + -12 = 3
-9x = 3

Divide each side by '-9'.
x = -0.3333333333

Simplifying
x = -0.3333333333

See similar equations:

| 2(-1)-3y=18 | | 4(5-b)=24 | | 6(-5+7d)=-30 | | 2(-2)-3y=18 | | 5(1a+6)=30 | | b-14.72=18.45 | | 4(4+3m)=16 | | 2(-5n+4)=-62 | | -20+x=x+16 | | 7(9+3m)=168 | | 4(-6t-1)=-148 | | 2(7-2t)=42 | | 3(9-2d)=3 | | df=g-10 | | 6(-2t+8)=-84 | | 7(-5+n)=-28 | | 4(2+a)=44 | | 6(2a+10)=96 | | 5(5+6n)=-215 | | 15a-54=-3 | | 7(-5+3k)=175 | | an=3+(n-1)(-5) | | (2x+10)=(86+x) | | 81=.5(9)h | | 76+x=180 | | X+7X-6=20 | | F(x)=-2x+2 | | 7(5w+8)=21 | | 2(3d+1)=-52 | | 4(-1+3d)=92 | | 5(4x+10)=190 | | 4(5+5t)=60 |

Equations solver categories